2002
DOI: 10.2337/diabetes.51.9.2871
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Susceptibility to the Molecular Causes of Neural Tube Defects During Diabetic Embryopathy

Abstract: Previously, we demonstrated that neural tube defects (NTDs) are significantly increased in a mouse model of diabetic pregnancy. In addition, expression of Pax-3, a gene encoding a transcription factor required for neural tube development, is significantly decreased. This suggests that diabetic embryopathy results from impaired expression of genes regulating essential morphogenetic processes. Here, we report that in one mouse strain, C57Bl/6J, embryos are resistant to the effects of maternal diabetes on NTDs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 23 publications
2
47
2
Order By: Relevance
“…In addition, multiple studies have demonstrated that the genetic susceptibility plays a key role in MM (2,5,20,21). Patients with genetically low FRSE activity are more susceptible to FRinduced damage (21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, multiple studies have demonstrated that the genetic susceptibility plays a key role in MM (2,5,20,21). Patients with genetically low FRSE activity are more susceptible to FRinduced damage (21).…”
Section: Discussionmentioning
confidence: 99%
“…Also, MM that is FR-mediated can be attributed to an increased FRs and decreased FRSE activity in the developing embryo. Many studies have demonstrated that antioxidants can prevent congenital malformations (2,20). Recent studies have shown that the addition of SOD or antioxidants to diet in culture helps to reduce the rate of embryonic anomalies (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Glut2 knockout strain was originally generated on a mixed C57Bl/6J×129/Sv background. C57Bl/6J embryos are resistant to diabetic embryopathy [36]. Therefore, a congenic strain was generated to place the Glut2 +/− allele on a 129/SvJ background [37].…”
Section: Methodsmentioning
confidence: 99%